DIGITALISASI PROSES BISNIS PETERNAKAN DENGAN IMPLEMENTASI SISTEM POINT OF SALES (POS) - Okky Putra Barus; Jefri Junifer Pangaribuan; Iskandar Muda; Chilwin Chilwin; Ricky Ricky; Sabrina Jovanka; Shendy Dennison; Yudhistira A. Pratama (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
One of the problems faced by MSMEs engaged in animal husbandry is the field of business management. Business management is still done traditionally, resulting in a merger of the company's operational funds and the manager's personal funds. This has an impact on the financial statements and the business decision-making process to be wrong. The solution that will be implemented to solve this problem is the digitization of livestock business processes by implementing a point of sales (PoS) system on 786 NS Farm located in Deli Serdang district, North Sumatra province. The implementation of the PoS system can help partners to record transactions digitally, make electronic books and produce financial reports that can assist partners in making decisions in the future. The PoS system implemented is the result of research by the proposing team, namely solutions that have obtained IPR with number No. Registration C00201702295 with the creation title "Officer Mobile Application". The results of this activity are learning the results of six months of mentoring to partners and increasing partner empowerment where partners are able to use the PoS system to record company operational transactions.